Effects of trimester-speciﬁc urinary aluminum concentrations on ultrasound measures of fetal growth and size at birth: A longitudinal cohort study in Chinese women - Haiying Chen; Wenjing Yan; Xueyan Wu; Yuanyuan Li (Ecotoxicology and Environmental Safety)
Objective: Aluminum (Al) has been proposed as a potential factor influencing fetal growth. However, the existing study findings are inconsistent and there is a lack of population-based epidemiological studies. Our study aimed to evaluate the trimester-specific correlations of Al exposure with fetal development characteristics. Methods: Between 2013 and 2016, 3599 women from Wuhan, China were enrolled in the prospective cohort study. The concentrations of Al were quantified in urine samples obtained from pregnant women during the 1st, 2nd and 3rd trimesters by inductively coupled plasma mass spectrometry. The study used linear regressions with generalized estimating equation to determine the connections between speciﬁc gravity-adjusted urinary Al concentrations in each trimester and fetal growth parameters and birth size indicators. Results: Trimester-specific Al exposure throughout pregnancy was found to have a negative impact on fetal growth and birth parameters. Besides, statistically signiﬁcant interactions were detected between biparietal diameter (BPD) (Pinteraction = 0.007), head circumference (Pinteraction = 0.026) at 16 weeks’ gestation in the first trimester, BPD (Pinteraction = 0.015) at 24 weeks’ gestation in the second trimester, BPD (Pinteraction = 0.014) at 31 weeks’ gestation in the second trimester and BPD (Pinteraction = 0.035) at 37 weeks’ gestation in the third trimester and fetal sex, and the strength of the association between the level of Al exposure and BPD was significantly stronger in female fetuses than in male fetuses. Furthermore, we observed three distinct trajectories of trimester-specific Al concentrations during pregnancy. Compared to participants with low-stable group of Al concentrations trajectory, high-stable group was associated with more decrease level of fetal growth parameters and birth size indicators. Conclusion: Our study results reveal that Al might have harmful effects on fetal growth and birth size indicators, especially in female fetuses. Further study is required to examine our findings in other populations.